Signs and Symptoms in Clinical Practice - Richhariya, D. Devendra; Tapia, J. D. L. Jesus Daniel López; Bajan, K. Khusrav; Sharma, B. Bhawana (Jaypee Brothers Medical Publishers, 2020)
The aim of this book is to focus on the sign and symptoms in clinical practice. Knowledge of clinical signs and symptoms are the ABCs of the medical education. Thorough knowledge of the signs and symptoms is the key to diagnosis of any disease. The book 'Signs and Symptoms in Clinical Practice' is for every acute care unit as well as various departments including emergency medicine, surgery, pediatrics, gynecology, orthopedics, psychiatry, cardiology, neurology, pulmonology and gastroenterology. This book consists of 91 chapters, enriched with knowledge of about more than 100 contributors. This book covers almost all the possible signs and the symptoms, commonly seen in the day-to-day clinical practice. It is compact, handy and bedside clinical companion book for all dedicated healthcare professionals. This book is helpful for undergraduates, postgraduates, residents, and emergency physicians.